Structural Analysis of Ut’aani as a Discursive Genre Present Among the Lacandon Maya of the Naja’ community, Chiapas (Andamios, Revista de Investigación Social, 2025)
Ut’aani are traditional discourses practiced by the Lacandon Maya who live in the three subcommunities comprising Lacandon territory: Metzabok and  Naja’, in the northwest, and Lacanjá Chansayab, in the south. The objective of practicing ut’aani is to propitiate or create a desired situation through the verbal formulas that structure it, as well as through repetitions –parallelisms– whose function is to synchronize the thought and voice of the speaker in order to manipulate reality and materialize it at will. The discourses analyzed for the purposes of this article were 41 ut’aani, compiled by a single Lacandon Maya speaker residing in the  Naja’ subcommunity.
Keywords: Lacandon Mayas; Mayan orality; International Relations Theory; Mayan rituals; ritual discourses; ut’aani